Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.ijrobp.2015.07.785
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Prognostic Factors Associated With Recurrence in the Treatment of Atypical Meningiomas

Abstract: Background: There has been increased reporting of atypical meningioma (grade II) since the World Health Organization reclassification in 2000, and the use of postoperative radiation therapy (RT) in the treatment of these tumors is controversial. We evaluated patients treated at our institution to identify patient subgroups with increased risk of recurrence that may benefit from adjuvant RT. Methods and materials: We retrospectively assessed 50 patients treated for World Health Organization grade II meningiomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
(19 reference statements)
1
4
0
Order By: Relevance
“…Thus, in cases of meningiomas with tumor volumes ˃ 26.4 cm3, the recurrence rate was higher than in the case of tumors with volumes below this value. This correlation between a larger size of the meningioma and the existence of the risk of tumor recurrence has also been observed by other authors in previous studies (16,17,19).…”
Section: The Influence Of Tumor Volume On the Tumor Recurrence Risksupporting
confidence: 88%
See 3 more Smart Citations
“…Thus, in cases of meningiomas with tumor volumes ˃ 26.4 cm3, the recurrence rate was higher than in the case of tumors with volumes below this value. This correlation between a larger size of the meningioma and the existence of the risk of tumor recurrence has also been observed by other authors in previous studies (16,17,19).…”
Section: The Influence Of Tumor Volume On the Tumor Recurrence Risksupporting
confidence: 88%
“…Fernandez et al reported that the size of over 4.5 cm of AM is associated with a risk of early recurrence (16). Moreover, Garzon-Muvdi et al also observed in his study that the size of the tumor can be considered an important factor not only for PFS, but also for overall survival.…”
Section: The Influence Of Tumor Volume On the Tumor Recurrence Riskmentioning
confidence: 89%
See 2 more Smart Citations
“…The most signi cant clinical factor is the extent of tumor resection, which is determined by the tumor location, extent of invasion, and skill of the surgeon (5). Fernandez (13) reported that atypical meningioma, female sex, subtotal resection, and tumor size exceeding 4.5 cm were associated with signi cantly higher recurrence rates. Regarding histopathological factors, the most useful predictor for recurrence is the WHO grade.…”
Section: Introductionmentioning
confidence: 99%